Expression and purification of recombinant omega-Conotoxin Mviia from E. coli - Huyen, Bui Thi; Bich Thao, Le Thi; Bich Nhi, Nguyen Thi; Chi, Phan Van (Academia Journal of Biology, 2012)
Following the strategy of cloning w-conotoxin MVIIA (w-CTX) from Conus magus (C. magus), in this article, the expression and purification of the peptide is reported. For that, recombinant plasmid CTXpET32c was designed containing fusion gene encoding thioredoxin (as original) and w-CTX (Trx-CTX) that is linked by enterokinase restriction site, was transformed into the E. coli BL21 strain. The fusion protein, Trx-CTX combined to 6xHis-tag, is about 21 kDa in size, was expressed by induction with 1 mM IPTG and analyzed by SDS-PAGE. The recombinant protein was isolated and purified by Sepharose chelating affinity chromagraphy. SDS-PAGE results were an evidence to confirm the successful construction and expression of w-CTX in the fusion form with Trx in E. coli with vector CTXpET-32c. When it was treated by enterokinase to remove thioredoxin, w-CTX peptide was purified and obtained by using 5 kDa cutoff centrifugal filters.